2018
DOI: 10.1371/journal.pone.0203306
|View full text |Cite
|
Sign up to set email alerts
|

Preservative effect of Chinese cabbage (Brassica rapa subsp. pekinensis) extract on their molecular docking, antioxidant and antimicrobial properties

Abstract: This study aimed at investigating the antimicrobial activity of different solvent extracts of Chinese cabbage Brassica rapa subsp. pekinensis (BRARP) and their antioxidant and cytotoxicity properties. Of the different solvents extracts, the chloroform extracts (CE) were significantly inhibited the bacterial pathogens at minimum inhibitory concentration (MIC) of 16.5 mg.mL-1. Biochemical analysis revealed that total phenol (62.6 ± 0.05 mg GAE.g-1) and flavonoids (27.6 ± 0.04 mg QE.g-1) were higher in the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
(58 reference statements)
5
20
0
Order By: Relevance
“…The inhibition activity of BRARP extract significantly increased ( p < .05) with an increase in the concentration of BRARP until 2%; however, there were as no significant difference between the fractions 2% and 2.5% ( p < .05). The results for antimicrobial activity of the BRARP extract which are indicated in Table confirm the results of previous studies, which reported that BRARAP possesses antimicrobial activity (Jarriyawattanachaikul, Chaveerach, & Chokesajjawatee, ; Patra & Baek, ; Rubab et al, ). In addition, there was no significant difference between the inhibition activities of 2% and 2.5% fraction against the targeted pathogens.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The inhibition activity of BRARP extract significantly increased ( p < .05) with an increase in the concentration of BRARP until 2%; however, there were as no significant difference between the fractions 2% and 2.5% ( p < .05). The results for antimicrobial activity of the BRARP extract which are indicated in Table confirm the results of previous studies, which reported that BRARAP possesses antimicrobial activity (Jarriyawattanachaikul, Chaveerach, & Chokesajjawatee, ; Patra & Baek, ; Rubab et al, ). In addition, there was no significant difference between the inhibition activities of 2% and 2.5% fraction against the targeted pathogens.…”
Section: Resultssupporting
confidence: 86%
“…The corresponding changes with and without BRARP extract had no significant difference ( p < .05) throughout the storage period. This could be attributed to the antioxidant potential of BRARP extract as reported previously (Rubab et al, ). However, the measured L* values show a statistically significant difference between the control and BRARP‐treated samples during storage, these effects on lightness were subjectively negligible.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations